Performance and emission study of low HCNG fuel blend in SI engine with fixed ignition timing. Issue 1 (31st December 2022) - Pandey, Vivek; Guluwadi, Suresh; Tafesse, Gezahegn Habtamu
Abstract: Natural gas (NG) has many advantages of clean fuels and can replace gasoline in spark ignition (SI) engines. However, it comes with disadvantages such as low energy density. Hydrogen blended NG can improve the fuel characteristics. Ignition timing also plays an important role in engine performance, especially at lean limits. Experiments were conducted for performance and emissions with hydrogen-compressed natural gas (HCNG) blends in a spark ignition (SI) engine with fixed ignition timing. HCNG blends with 0–15% hydrogen were tested with maximum brake torque (MBT) spark timing 30° before top dead center (BTDC) ignition. Significant reduction of carbon monoxide (CO), carbon dioxide (CO2 ) and hydrocarbons (HC) along with improved break thermal efficiency was observed with higher hydrogen fraction. There was no significant benefit in indicated thermal efficiency or NO x reduction by using MBT ignition. Hence, the expensive retrofitting of using variable spark timing apparatus can be avoided for on-road vehicles.